Load Encroachment in the Presence of Single-Phase Autoreclosure and Bulk Power Transmission - Prommetta, Jonas; Schindler, Jakob; Jäger, Johann; Romeis, Christian; Keil, Timo (2021 IEEE Madrid PowerTech, PowerTech 2021 - Conference Proceedings, 2021)
The paper discusses how the asymmetrical situation during single-phase autoreclosure influences the protection security and line loadability. First, we analyze the phase current displacement and earth current in single-phase and three-phase tripped conditions and their dependence on system impedance parameters. We then show the effects on the conventional distance protection algorithm and give worst case estimates for the reduction of measured impedance in asymmetrical cases. Simulations using PSCAD and a Digital Twin of Siemens distance relays are presented to give a good assessment of relay behavior and protection security. Lastly, we discuss possible solutions like reduced zone-reach of phase-to-earth loops and use of reactance method.
CRIS-Team Scopus Importer:2021-08-20
Keywords: load encroachment; protection algorithm; protection security; relay loadability; single-phase autoreclosure